Makna Quarter Life Crisis : Studi Fenomenologi Pemuda Gereja Kristus Gunung Putri - Ndraha, Yalimurni; Nayiroh, Luluatu; Utamidewi, Wahyu (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out about the meaning of the Quarter Life Crisis and whether there is an influence from the environment as well as communication among the youth of Christ Gunung Putri church. The method used in this study uses qualitative methods in this study, namely researchers use descriptive data that uses several words, either written or spoken, by behavior and people who will be observed. The approach used is phenomenology to understand the meaning of the Quarter Life Crisis among the youth of the Christ Gunung Putri Church. The informants in this study were young members of the Christen Gunung Putri church aged 18-29 years who were going through the Quarter Life Crisis phase. The results of this study consist of two main issues, namely regarding the meaning of the Quarter Life Crisis and its influence on communication among the youth of Christ the Gunung Putri church. With the experiences felt by the informants raises questions that refer to how the meaning of the Quarter Life Crisis is in the communication of the youth of the church of Christ the Gunung Putri. Based on the direct experience experienced by the informants about the Quarter Life Crisis phase, it produces various meanings. This meaning is of course related to one's background, age, communication patterns, and responses from the surrounding environment. Quarter Life Crisis as a phase of crisis at the age from adolescence to adulthood, which they are generally experiencing at this time. Feelings of anxiety, worry about the future, confusion, searching for identity, feeling insecure and having many demands they feel at this time. Of course, all informants had conducted intrapersonal communication (by struggling with themselves for any concerns as well as making decisions) and also interpersonal (sharing with fellow youth members which resulted in comfort, relief and helpful inside) during the Quarter Life Crisis phase. Keywords: Quarter Life Crisis, intrapersonal communication, interpersonal communication